ChemInform Abstract: New Compounds from Tabebuia avellanedae. Issue 32 (24th July 2014) - Tadano, Takeshi; Zhang, Li; Hasegawa, Isao; Tatsuno, Takanori; Ohta, Tomihisa; Kawabata, Tetsuro
Abstract: Two new compounds (I) and (II) are isolated and their structures are fully characterized.